Challenges and Prospect of Security Intervention in Armed Conflict in Benue State-Nigeria - Tanko Shawulu Paul; Sani Inusa Milala (Jurnal Restorasi : Hukum dan Politik, 2025)
The new dimensional conflicts between farmers and herders in this 21st Century is concentrated in the Northeast, Northwest and North Central regions of Taraba, Kaduna, Plateau, Nasarawa, and Benue States possibly for peculiar reasons. The Middle Belt region of Nigeria (North Central geopolitical) region is an area where the indigenous people are predominantly farmers while the settlers (mainly Fulani) are known for their cattle breeding and pastoral activities. Social and economic factors continue to trigger violent conflicts among the herdsmen and farmers, each group struggling to hold dominance. Three factors have aggravated this decades-long conflict arising from environmental degradation in the far north and encroachment upon grazing grounds in the Middle Belt: militia attacks; the poor government response to distress calls and failure to punish past perpetrators; and new laws banning open grazing in Benue and Taraba states. This research examined the challenges of security intervention in armed conflict in Benue state. The research focused on Benue state. The research is broken into five chapters. The researcher Adopt Eco-Violence theory. Survey research design was used as methodology. Descriptive statistic was used for data presentation. The researcher recommend that Ranching should be encourage so as to avoid further clashes between farmers and herdsmen, conflict management committee should be set up by Government to deal with farmers/herders’ conflict, stake holders should be involved dialogue to avoid future happening.